POTRET POLITIK ANGGARAN (Studi Kasus tentang Alokasi Belanja Modal Pada APBD Kabupaten Halmahera Barat Periode 2011-2015) - Maslan Adam (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
This study aims to describe the budget politics on the government capital expenditure in West Halmahera Regency. This study uses a qualitative approach, with interactive analysis models of Milles and Huberman. The study found that there was a 'top level' leadership policy that often distorted the value of budget allocations, thus implicating the allocation of capital expenditures that could not be increased to 30 percent. On the other hand, low fiscal capacity makes it difficult for local governments to increase the allocation of capital expenditures in accordance with the provisions of statutory provisions. Based on these findings, it is recommended that the local government together with the DPRD of West Halmahera Regency be committed to practicing a performance-based planning and budgeting system by taking into account the principle of money follow Programme .